Analysis of the resistance of M. tuberculosis to fluoroquinolon and the implementation of nuclear based biomolecular technique. - Mukh Syaifudin; Dewi Septiani (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Tuberculosis (TB) is still a problem in community health with high rate of mortality. The case became much more complicated due to emerge of Mycobacterium tuberculosis which are resistant to the drugs. This caused the movement of attention from the first line drugs to fluoro-quinolon (FQ) as alternative drug. The aim of this research was to do analysis the mutation which causing the resistance of bacterial through nucleic acid alterations with polymerase chain reaction (PCR) and single strand conformation polymorphism (SSCP) technique. Analysis was done on gyrA and gyrB genes encoding DNA gyrase of bacterial and closely related to FQ resistance in 100 of sputa samples of positive BTA test results. DNA of M. tuberculosis strain H37Rv was used as control. From analysis on gyrA gene it was known that 57 samples were positive PCR and no resistant sample was found. For gyrB gene, only 12 of them were positive PCR and again there was no samples had mutation as cause of resistance. These mean that FQ could be used as replacement drug. Molecular detection technique was known fast and specific for assessing bacterial resistance. Researcher proves that searching for P32-radioisotope labeled DNA alteration was more sensitive. Hopefully this results of experiment can be implemented in medication with more effective and support diagnose results so that it will lowering the risk of patient mortality.Key words : M. tuberculosis, fluoro-quinolon, resistance, PCR, SSCP